SYNTHESIS OF SOME FERROCENE DERIVATIVES - Ibrohim Asqarov; Qobiljon Otakhonov; Gayratjon Madrahimov; Ilyosbek Avazbekov (American Journals Publishing, 2024)
The article provides information on the production of ferrocene and its derivatives, their physical and chemical properties, and their practical importance. Also, the synthesis of the derivative of o-ferroceny lbenzoic acid with dimethylolthiourea - 1-(2-carboxyphenyl)-1'-N-(ferrocenylmethyl)-N'-methyloxycar -boxamide, its structure and chemical composition was given.
Keywords: Ferrocene, cyclopentadienyl ring, aromaticity, ferrocenium ion, nitration, sulfation, organometallic compound, acetic anhydride, copper halides, aminobenzoic acids, biological activity, ferrocenyl nucleus, arylation, alkylation, acylation, elemental analysis.